2012
DOI: 10.3390/s120302851
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Characterization, and Biological Effect of Quorum-Sensing Signaling Molecules in Peanut-Nodulating Bradyrhizobia

Abstract: Bacteria of the genus Bradyrhizobium are able to establish a symbiotic relationship with peanut (Arachis hypogaea) root cells and to fix atmospheric nitrogen by converting it to nitrogenous compounds. Quorum sensing (QS) is a cell-cell communication mechanism employed by a variety of bacterial species to coordinate behavior at a community level through regulation of gene expression. The QS process depends on bacterial production of various signaling molecules, among which the N-acylhomoserine lactones (AHLs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 66 publications
5
30
0
Order By: Relevance
“…Biofilm formation capacity was determined macroscopically (Nievas et al, 2012). Briefly, glass tubes were inoculated with 800 ml LB medium (OD 600 0.5) and incubated with shaking for 24 h at 37 uC.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation capacity was determined macroscopically (Nievas et al, 2012). Briefly, glass tubes were inoculated with 800 ml LB medium (OD 600 0.5) and incubated with shaking for 24 h at 37 uC.…”
Section: Methodsmentioning
confidence: 99%
“…In certain species, the biofilm formation is an important feature for colonization and/or host invasion (Nievas et al 2012;Perez-Montano et al 2014). The biofilm formation assay performed on E. meliloti 3001 revealed that luteolin affected the biofilm formation on rich medium and minimal medium (Fig.…”
Section: Influence Of Luteolin On Biofilm Formation Of E Meliloti 3001mentioning
confidence: 99%
“…The ICDs for which a significant reduction, t test, P < 0.05 or t test, P < 0.01, of lag time induced by luteolin was detected are marked with * or **, respectively. ICDs for which statistical analysis was not performed, since the lag time of untreated cultures (0 μM luteolin) was higher than 90 h, are marked as Bnd^(not determined) Effect of luteolin on motility proficiency In rhizobia, motility has been shown not to be essential for nodulation, but it allows the bacteria to find their specific host legume and establish symbiosis (Nievas et al 2012). Bacterial motility is an energetically costly process, and therefore must be finely regulated (Nievas et al 2012).…”
Section: Influence Of Luteolin On Indole-3-acetic Acid (Iaa) Productionmentioning
confidence: 99%
“…QS positively regulates the auto-aggregation (or co-aggregation) process, enhancing the survival of microorganisms and attachment to the substratum (Nievas, Bogino, Sorroche, & Giordano, 2012). The aggregation process is beneficial for aerobic granule (AG) formation.…”
Section: Cell Differentiation and Monolayer Synthesismentioning
confidence: 99%